Creating and running an Agile Project in JIRA - Harned, David (Packt Publishing, 2018)
"JIRA Software is an agile project management tool that supports any agile methodology, be it scrum, Kanban, or your own unique flavor. From agile boards to reports, you can plan, track, and manage all your agile software development projects from a single tool. JIRA Software brings the power of the agile methodology to Atlassian's JIRA Software. With this course, you will dive straight into the action, exploring critical agile terminologies and concepts in the context of JIRA Software. You will learn how to plan, track, and release great software. This course will teach you how to choose a workflow, set issue types and assign permissions. You will learn to stay connected with your team from anywhere to ensure great development. You will also be able to use JIRA Dashboards to broadcast your project results to all stakeholders so everyone is aligned. By the end of this course, you will have developed a great working knowledge of JIRA Software, thus making your project management much more efficient."--Resource description page